Analysis of the risk and risk factors for injury in people with and without dementia: a 14-year, retrospective, matched cohort study - Chen, Ruey; Chien, Wu-Chien; Kao, Ching-Chiu; Chung, Chi-Hsiang; Liu, Doresses; Chiu, Huei-Ling; Chou, Kuei-Ru (Alzheimer's research & therapy, 2018)
Most previous studies on dementia and injuries have focused on a particular type of injury, and few studies have investigated overall injury in people with dementia. In this study, we investigated the risk factors and risk of overall injury, including the diagnosis, cause, and intentionality of injury, in people with and without dementia in Taiwan. We collected relevant data between 2000 and 2013 from the National Health Insurance Research Database (NHIRD). Overall, 455,630 cases, consisting of 91,126 people with dementia and 364,504 people without dementia, were included in this study and we performed subgroup analysis. A multivariate Cox proportional hazards regression analysis was used to determine the risk of injuries. The 14-year follow-up data showed that people with dementia had a higher risk of injury-related hospitalization than did people without dementia (19.92% vs 18.86%, hazard ratio (HR) = 1.070, p < 0.001). Regarding the cause of injury, people with dementia were more likely to be hospitalized due to suffocation (HR = 2.301, p < 0.001), accidental drug poisoning (HR = 1.485, p < 0.001), or falls (HR = 1.076, p < 0.001), and were less likely to be hospitalized due to suicide or self-inflicted injury (HR = 0.670, p < 0.001) or a traffic accident (HR = 0.510, p < 0.001) than were people without dementia. Subgroup analysis showed that people with dementia with any of the three subtypes of dementia were at a higher risk of homicide or abuse than were people without dementia (vascular dementia, HR = 2.079, p < 0.001; Alzheimer's disease, HR = 1.156, p < 0.001; other dementia, HR = 1.421, p < 0.001). The risk factors for overall injury included dementia diagnosis, female gender, age 65-74 years, and seeking medical attention for an injury within the past year. People with dementia are at a higher risk of injury-related hospitalization than people without dementia. The results of this study provide a reference for preventing suffocation, drug poisoning, and falls in people with dementia. In addition, government agencies should pay attention to and intervene in cases of abuse suffered by people with dementia.